2001
DOI: 10.1159/000050139
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Rupture following ESWL for a Pancreatic Duct Calculus

Abstract: Extracorporeal shock wave lithotripsy (ESWL) is an established and extensively used treatment alternative for urinary calculi. It is also an established method of dealing with pancreatic duct calculi complementing endoscopic techniques in selected cases. Three reports of splenic injury following and probably caused by ESWL for urinary calculi have previously been published. We report a case of splenic rupture presenting with life-threatening hemorrhage 6 days after a single ESWL therapy session for pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…A decrease in the use of analgesics and hospitalization has been reported earlier [18]. Though a wide range of complications have been reported with ESWL [25][26][27], these were minimal in this series and there was no mortality. The use of epidural anesthesia and sharp focusing achieved with the 3rd generation lithotripter decreases collateral tissue damage and reduces the rate of complications.…”
Section: Discussionsupporting
confidence: 50%
“…A decrease in the use of analgesics and hospitalization has been reported earlier [18]. Though a wide range of complications have been reported with ESWL [25][26][27], these were minimal in this series and there was no mortality. The use of epidural anesthesia and sharp focusing achieved with the 3rd generation lithotripter decreases collateral tissue damage and reduces the rate of complications.…”
Section: Discussionsupporting
confidence: 50%
“…10,27,28 In our series, we showed that the implementation of technical improvements (ie, location system and focusing) achieved with the latest generation of lithotripters further reduced the incidence of adverse events, particularly the incidence of serious adverse events.…”
Section: Discussionmentioning
confidence: 73%
“…In our patient, the presence of unrecognized vascular anomalies might be promote ischemic necrosis of the biliary tree. Nevertheless, we cannot exclude a direct effect of ultrasound waves due to adhesion between the kidney and surrounding tissues (13). Indeed, signs of inflammatory and traumatic processes of the biliary tract were present during nephrectomy.…”
Section: Discussionmentioning
confidence: 91%